Exposure to large-scale farms increases smallholders' competitive behavior and closes the gender gap - Menusch Khadjavi; Kacana Sipangule; Rainer Thiele (World Development, 2024)
We investigate how exposure to large-scale farms affects smallholders' competitive behavior. Based on lab-in-the-field experimental measures covering more than 900 smallholders and 400 children in Zambia, we find that smallholders who are traditionally dependent on subsistence agriculture behave more competitively when they are located close to large-scale farms. This effect is especially pronounced for female smallholders and closes the gender gap associated with competitiveness. This result replicates for their children. We identify female employment and shifting intra-household tasks as a possible mechanism. Our results provide new insights for understanding how changes in societal arrangements like market integration influence economic behavior.
Keywords: O12; O13; P11; P14; Q15; 330; Market integration; Competitive behavior; Large-scale farms; Smallholders; Endogenous preferences; Lab-in-the-field experiment; Zambia